2018
DOI: 10.1002/ijc.31862
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and determinants of follow‐up colonoscopies within 6 years after screening colonoscopy: Prospective cohort study

Abstract: Previous studies have reported that repeat colonoscopies were often not conducted in the recommended time interval after screening colonoscopy. We prospectively followed participants of screening colonoscopy from Germany for 6 years to investigate utilization and determinants of repeat colonoscopies. In a longitudinal study on the effectiveness of screening colonoscopy in the state of Saarland (Germany), participants who had a screening colonoscopy between 2005 and 2007 were contacted by mail 6 years after scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(98 reference statements)
2
14
0
1
Order By: Relevance
“…A recent study from Germany including 6,407 persons showed substantial overuse of repeat colonoscopies in persons with negative findings and underuse in persons with low- and high-risk adenomas at baseline. However, that study was restricted to screening participants and to a follow-up of 6 years ( 6 ). Studies from Australia, Canada, and the United States showed similar patterns but were also restricted to participants of screening colonoscopy ( 5 , 8 , 10 , 13 ) or considered any colonoscopy, i.e., screening and diagnostic colonoscopies combined ( 3 , 4 , 7 , 9 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Germany including 6,407 persons showed substantial overuse of repeat colonoscopies in persons with negative findings and underuse in persons with low- and high-risk adenomas at baseline. However, that study was restricted to screening participants and to a follow-up of 6 years ( 6 ). Studies from Australia, Canada, and the United States showed similar patterns but were also restricted to participants of screening colonoscopy ( 5 , 8 , 10 , 13 ) or considered any colonoscopy, i.e., screening and diagnostic colonoscopies combined ( 3 , 4 , 7 , 9 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…For opportunistic screening programs, further increases in screening adherence are to be expected when an organized screening program with personal invitations is introduced . An organized screening program including invitation of the target population could also help to reduce both underuse and overuse of screening and surveillance colonoscopies, which are major issues in the current opportunistic screening program in Germany …”
Section: Discussionmentioning
confidence: 99%
“…27,28 An organized screening program including invitation of the target population could also help to reduce both underuse and overuse of screening and surveillance colonoscopies, which are major issues in the current opportunistic screening program in Germany. 29 Our study has a number of specific strengths and limitations. A major strength is the unique possibility to address screening use in both cross-sectional and longitudinal manner based on a large, statewide cohort study of older adults recruited shortly before introduction of screening colonoscopy as an alternative CRC screening offer.…”
Section: Discussionmentioning
confidence: 99%
“…The German Guideline Program in Oncology cites one small repeat colonoscopy study from 1996 with a mean interval between examinations of 5.5 years,3 as well as further indirect evidence from case-control studies, in which cases were composed of only participants with colorectal cancer 45 Moreover, despite these guideline recommendations, several studies have suggested considerable overuse of repeat screening colonoscopy before the end of the recommended interval 67 8 9 10…”
Section: Introductionmentioning
confidence: 99%